Milk Yield of Dairy Buffaloes Supplemented with Yeast Solution and Yeast-fermented Cassava Pulp - Emerson Pilongo Tapdasan; C B Salces; A J Salces (Jurnal Ilmu Ternak dan Veteriner, 2022)
Feed resource availability and quality are two of the major factors limiting dairy production in the Philippines. Utilization of microbial-based feed additives and agricultural by-products such as cassava pulp aided by fermentation technology can help provide the needed resource. This study aimed to determine the effect of activated yeast (Saccharomyces cerevisiae) solution (AYS) and yeast-fermented cassava pulp (YFCP) on milk production and feed cost-efficiency in dairy buffaloes. The study followed RCBD design using 63 dairy buffaloes at the Philippine Carabao Center in Ubay Stock Farm, Bohol. The average daily milk yield (ADMY) of buffaloes supplemented with 0.5L AYS and 1L AYS twice daily were greater than that of control buffaloes by 0.67L and 0.69L, respectively (P = 0.0039).On the other hand, the ADMY of buffaloes fed with YFCP and YFCP+AYS were greater than that of control buffaloes by 0.64 and 0.68L, respectively (P = 0.0320). Supplementation of AYS and feeding YFCP yielded the lowest cost per liter of milk produced at PhP 20.25 and PhP 16.24, respectively. It is recommended to supplement milking dairy buffaloes with AYS or feeding YFCP in areas with cassava pulp to increase feed resource, increase milk production and improve feed cost-efficiency thereby increasing significantly the farmer’s income.